KEAMANAN DATA DALAM PROSES PEMILU 2024: IDENTIFIKASI DAN MITIGASI ANCAMAN KEBOCORAN DATA ELEKTORAL - Hadad, Alwi Al (Jurnal Keadilan Pemilu, 2023)
Data security in the election process is a crucial aspect of maintaining integrity and public trust in democracy. The threat of electoral data leaks could have serious consequences for individual privacy and the legitimacy of election results. This article discusses steps to identify and mitigate data security threats in the 2024 election. This process begins with a thorough risk assessment to identify potential threats and data sensitivity values. Integrated solutions involve implementing end-to-end data encryption, network protection with firewalls and intrusion detection systems, and regular security system updates. The importance of security awareness training for election personnel and conducting regular security audits was also emphasized. Strict management of access rights, development of emergency response plans, and collaboration with trusted third parties are also a focus. Overall, this approach is aimed at minimizing the risk of data leaks, improving election security, and building public trust in the democratic process.